Influence of two types of diets on size and body weight in Crocodylus acutus, Cuvier 1807 neonates (Crocodylidae: Crocodylia) of Manzanillo Nursery, Cuba. - Pérez Gómez, Mario; Naranjo López, Carlos; Reyes Tur, Bernardo; Vega Ramírez, Irene (Instituto de Ecología, A.C., 2009)
An experiment was designed with 90 neonates of the American crocodile, Crocodylus acutus, that were raised and fed with a standard diet during 50 days and with two experimental diets for 30 days, in three groups (A, B, C) kept in experimental square tanks during 30 days at the Manzanillo Zoocriadero (Province of Granma). The influence on size and body weight increase of two types of diets against the standard diet in C. acutus was analyzed, as well as the economic costs associated. The sea fish diet (B) is more effective compared to the standard diet of fish, cow liver and lung (A) and to the fly maggot diet (C), since the growth rate of neonates was 35 mm /day, growing 1.35 times more. The weight increase was 3.71 g/day, higher than the increases obtained with the other two diets. It was demonstrated that with diet B neonates grew 1.35 times more than with the diets A and C. However, each neonate fed with diet B costs 14 times more than those fed with the other two diets